Effects of Covid-19 Pandemic On the Mental Health of Employees in Ghana: The Moderating Role of Social Capital - Baidoo, Francis; Kwatemaa, Rita (Journal of Medical Health Research and Psychiatry, 2024)
The study examined the impact of social capital in moderating the effects of the Covid19 pandemic on workers' mental health. We posited that their level of social capital influences workers’ mental health during the Covid19 crisis. Data was sourced from a cross-sectional survey of 422 employees from various industries in Ghana, analyzed using partial least squaresbased structural equation modelling (PLS-SEM). Results indicated that the pandemic adversely affected employees' mental well-being, increasing anxiety levels. However, a higher degree of social capital within the workplace buffered these negative effects, enhancing mental health during this period. Essentially, strong workplace relationships and networks mitigated the pandemic's impact on employees' mental health in Ghana. These findings underscore the importance of social capital in health outcomes, especially during crises. For industries in Ghana and beyond, the results emphasize the value of fostering strong social networks. In times of health crises, such as the Covid19 pandemic, robust social ties become crucial. As we navigate the aftermath of this pandemic and prepare for potential future crises, the lessons from this research highlight the need to integrate the knowledge gained from the Covid19 experience into our disaster response strategies. The role of social capital in such scenarios cannot be overstated.